2018
DOI: 10.1016/j.neuropharm.2018.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to environmental enrichment attenuates addiction-like behavior and alters molecular effects of heroin self-administration in rats

Abstract: Environmental factors profoundly affect the addictive potential of drugs of abuse and may also modulate the neuro-anatomical/neuro-chemical impacts of uncontrolled drug use and relapse propensity. This study examined the impact of environmental enrichment on heroin self-administration, addiction-related behaviors, and molecular processes proposed to underlie these behaviors. Male Sprague-Dawley rats in standard and enriched housing conditions intravenously self-administered similar amounts of heroin over 14 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 89 publications
2
38
0
1
Order By: Relevance
“…The protective effects of environmental enrichment were further demonstrated in a 2018 study where enriched rats had access to a variety of objects and a running wheel. Animals in the enriched housing condition acquired a similar level of heroin self-administration, but showed reduced motivation to consume heroin and relapse propensity in progressive ratio and reinstatement tests (39). These studies conceptually replicate the key findings of the Rat Park studies and Hill and Powell's experiments, demonstrating that across different opioid reinforcers and research groups, social and environmental enrichment reduce addiction-like behaviours in animals.…”
Section: Conditioned Place Preference: Stimulantssupporting
confidence: 65%
“…The protective effects of environmental enrichment were further demonstrated in a 2018 study where enriched rats had access to a variety of objects and a running wheel. Animals in the enriched housing condition acquired a similar level of heroin self-administration, but showed reduced motivation to consume heroin and relapse propensity in progressive ratio and reinstatement tests (39). These studies conceptually replicate the key findings of the Rat Park studies and Hill and Powell's experiments, demonstrating that across different opioid reinforcers and research groups, social and environmental enrichment reduce addiction-like behaviours in animals.…”
Section: Conditioned Place Preference: Stimulantssupporting
confidence: 65%
“…It could be that transcription start sites and CG islands were hypermethylated and flanking regions were hypomethylated, or vice versa, and thus these two effects cancelled each other out. As Imperio et al [ 5 ] showed, heroin administration to rats revealed no differences in total genomic methylation, but induced site-specific hypo-methylation in EGR1 and EGR2. Moreover, differential methylation was observed in six nuclear-encoded genes in different rat brain regions, following acute and chronic morphine administration [ 4 ].…”
Section: Discussionmentioning
confidence: 97%
“…Both acute and chronic morphine exposure have been associated with brain region-specific changes in 5-mC and 5-hmC levels [ 4 ]. Moreover, gene specific hypo-methylation has been reported to coincide with heroin use disorder in animal models and has been associated with the treatment and prevention of opioid use [ 5 ]. An epigenome-wide association study that was conducted in 220 European-American women revealed three differentially methylated regions associated with genes PARG, RERE, and CFAP77 [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the effects of EE on nicotine-induced CPP in male rats were assessed and the results indicated that, in enriched conditions, rats showed extinction of the nicotine-induced CPP response by the 5th extinction session (Ewin et al 2015). Also, while animals in standard and enriched housing conditions intravenously selfadministered similar amounts of heroin over 14 days, EE diminished extinction response in male Sprague-Dawley rats (Imperio et al 2018). In addition, 30 days of EE significantly and consistently reduced cocaine seeking behavior during extinction sessions and significantly reduced cue and stressinduced reinstatement of cocaine self-administration (Chauvet et al 2009).…”
Section: Discussionmentioning
confidence: 99%